2012
DOI: 10.1007/978-3-642-25789-6_66
|View full text |Cite
|
Sign up to set email alerts
|

White-Box Test Case Generation Based on Improved Genetic Algorithm

Abstract: Abstract. Some intermittent or transient failures are particularly difficult to diagnose in highly complex and interconnected systems. This paper focuses on the use of genetic algorithms for automatically generating software test cases. In particular, this research extends a newly improved genetic algorithm, which adopts back propagation algorithm for local fine-tuning in the final link, and speeds up access to the best population. The various approaches offer opportunities for performance improvements that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…By addressing the issues caused by concurrency in object-oriented software, Khandai et al [4] suggested a technique for creating test suites via sequence diagrams (SDs). In this study, Wang et al [5] concentrated on applying evolutionary algorithms for automatically implementing test suites.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By addressing the issues caused by concurrency in object-oriented software, Khandai et al [4] suggested a technique for creating test suites via sequence diagrams (SDs). In this study, Wang et al [5] concentrated on applying evolutionary algorithms for automatically implementing test suites.…”
Section: Literature Reviewmentioning
confidence: 99%